PENGARUH BEBAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KEPUASAN KERJA PADA PT. PERKEBUNAN NUSANTARA VI - Ahmad Fajar Sidiq; Robby Dharma; Selvi Yona Sari (Yayasan Tri Edukasi Ilmiah, 2024)
This study aims to determine how much influence workload and organizational commitment have on organizational citizenship behavior with job satisfaction as an intervening variable. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 3.0. By circulating the questionnaire as many as 75 respondents. The results of the data analysis concluded that workload had a positive and insignificant effect on job satisfaction. Organizational commitment had a positive and significant effect on job satisfaction. Workload had a positive and significant effect on organizational citizenship behavior. Organizational commitment had a positive and insignificant effect on organizational citizenship behavior. Job satisfaction has a positive and significant effect on organizational citizenship behavior. Workload has a positive and insignificant effect on organizational citizenship behavior through job satisfaction. Organizational commitment has a positive and significant effect on organizational citizenship behavior through job satisfaction.